O processo de construção da direção de arte audiovisual: uma investigação - Pires, Julia Vieira (Universidade do Vale do Rio dos Sinos, 2019)
The present work seeks to understand the work of the professional Audiovisual Art Direction. In order to do this, it seeks in a theoretical and empirical way to dive into the reality of this professional, an audiovisual art direction experiment,the short film "Mandrágora". Based on the theoretical concepts of aesthetics, cinematographic aesthetics and cinematographic art direction, the research is developed through the methodologies of bibliographical research, in-depth interview with professionals in the area of audiovisual art direction, field diary and experiment. After a comparison of the concept defined in an art book and the execution of the experiment, the results shows that the work of the audiovisual art direction is more than creativity, but also very technical and mutable.
Keywords: Direção de arte; Cinema; Audiovisual; Estética cinematográfica; Concepção visual; Art direction; Movie theater; Audiovisual; Cinematographic aesthetics; Visual conception